“A Place Not Made by Hands”: Unsteady Formations of Nationalist Religiosities in Malawi - R. Drew Smith (Religions)
This article focuses on the Christian ecclesiastical footing and moorings of nationalist thought and pursuits within colonial Nyasaland and its postindependence iteration as the nation of Malawi. Attention is paid to foundational influences and the impact of European mission churches, beginning in the late 1800s, and three streams of American Christianity that influenced social development in Malawi: (1) historic African American Methodist and Baptist traditions; (2) Watchtower millenarianism; and (3) emerging mid-1900s expressions of predominantly white Pentecostal, charismatic, and evangelical Christianity. The article examines ways these European and American religious streams served as crucial catalysts for one or another form of African independency within the Malawi context, paying particular attention to the ways and degrees to which African innovations on Global North Christian expressions and paradigms proved disruptive to established authorities.